To B or not to B. The rationale for quantifying B‐lines in pediatric lung diseases. Issue 1 (25th October 2022) - Parri, Niccolò; Allinovi, Marco; Giacalone, Martina; Corsini, Iuri
Abstract: Lung ultrasound (LUS) is emerging as adjunct tool to be used during clinical assessment. Among the different hallmarks of LUS, B‐lines are well known artifacts, which are not correlated with identifiable structures, but which can be used for pathological classification. The presence of multiple B‐lines is a sonographic sign of lung interstitial syndrome. It has been demonstrated in adults that there is a direct correlation between the number of B‐lines and the severity of the interstitial involvement of lung disease. Counting B‐lines is an attempt to enrich the clinical assessment and clinical information, beyond obtaining a simple dichotomous answer. Semiquantitative or quantitative B‐line assessment has been shown to correlate with fluid overload and demonstrated prognostic implications in specific neonatal and pediatric conditions. LUS with quantitative B‐lines assessment is promising. Current evidence allows for quantification of B‐lines in a limited number of neonatal and pediatric diseases.